Growth-controlled from SnO2 nanoparticles to SnO nanosheets with tunable properties. (5th August 2016) - Salah, Numan; AL-Shawafi, Waleed M.; Habib, Sami S.; Azam, Ameer; Alshahrie, Ahmed
Abstract: Tin oxide has excellent properties for a wide range of applications. It exists in two forms, stannic (SnO2 ) and stannous (SnO). This work describes a new approach for producing these forms in nanoscale dimensions using the chemical microwave assisted route. The oxidation state and morphology of tin oxide were simultaneously controlled in aqueous solution by varying the molar ratio of tin chloride and hexamethylenetetramine within the range 1–8:20. Fine nanoparticles of SnO2 were formed at the low ratios, whereas SnO grew at higher ratios in the form of nanosheets. The SEM, TEM and XRD results revealed detailed information about the morphological and microstructure properties of these nanostructures. The energy band gaps were found to be tunable relative to the molar ratio of the starting compounds. Resistivity measurements and activation energy calculations were found to be in the range 191–7.3 Ω·cm and 1.46–0.73 eV, respectively for the samples produced at the molar ratios 1–8:20. The formed SnO nanosheets and SnO2 nanoparticles were found to have tunable positive and negative Seebeck coefficients, respectively. The mechanism of nanostructures formation/oxidation was explained using a model called "surfactant stress model". These nanostructures with their tunable properties might be useful for variety of applications. Graphical abstract: Highlights: A new approach to synthesize SnO2 and SnO nanostructures has been described. Their oxidation state and morphology were simultaneously controlled. The microwave route is used by varying the molar ratio of the starting compounds. Fine SnO2 nanoparticles and SnO nanosheets were grown by varying this ratios. These structures have tunable structural, optical and thermoelectrical properties.